Uneven Pathways to Local Power: The Political Incorporation of Immigrants’ Descendants - Robin Stünzi; Rosita Fibbi; Gianni D'Amato (Politics and Governance)
Research focusing on the political incorporation of immigrants’ descendants is rather scarce, in contrast to the high level of scholarly attention paid to the case of foreign-born immigrants. This exploratory study addresses this gap by adopting a sociological and neo-institutionalist approach to investigate the trajectories leading to political involvement of children of immigrants elected to local parliaments across a selection of Swiss cantons. The analysis of the factors shaping their mobilization in relation to the features of local policies for immigrants’ integration and cantonal conceptions of citizenship sheds light on the variability of their political incorporation. The article thus makes a twofold contribution to the existing literature. First, it highlights the distinctive role played by local schools in the political socialization of immigrants’ descendants, compared to that of their Swiss-origin counterparts. Second, it shows the decisive impact of cantonal institutional and discursive contexts in shaping the categories that are relevant for political action, influencing collective identities, claim-making, and political mobilization.